Hubungan Antara Efikas1 Diri dengan Minat Berwirausaha pada Mahasiswa Tingkat Akhir Fakultas Psikologi Universitas Muhammadiyah Surakarta - Agustina, menik; , Susatvo Yuwono, S.Psi M.Si.Psikolog (2016)
The high unemployment rate in Indonesia occurred due to the orientation of college graduates are still many who want the job position as a public servant and trying to be an employee of a government agency is considered in accordance with the capabilities, so very few who have an interest berwirausaha.n therefore need to be sought factors that may affect the interest in entrepreneurship, and one of these factors is self-efficacy. So the authors propose the hypothesis "there is a positive relationship between self-efficacy with interest in entrepreneurship". This study aims to determine the relationship between self-efficacy. interest in entrepreneurship This study uses a quantitative method in which the self-efficacy variable is the independent variable and the dependent variable is the interest in entrepreneurship Subjects used in this study were students of the Faculty of Psychology final level totaling 241 students with incidental sampling technique, and the sample of 100 people. Peirgumpulan method of data used is the self-efficacy scale and scale of interest in entrepreneurship. Methods of data analysis conducted by using product moment correlation technique. The results showed no significant positive correlation between self-efficacy with interest in entrepreneurship where the value of the correlation coefficient (r) A sum of 0.409 with sig: 0.000, P <(0.01). Based on the analysis, it is known that the average empirical (RE) self-efficacy which is equal to 42.28 and the mean hypothetical (RH) of 42.5, which means efficacy study in subjects classified as moderate. While variable interest in entrepreneurship has the empirical mean (RE) of 92.63 and the mean hypothetical (RH) of 87.5, which means interest in entrepreneurship in the research subject is high. Sumbangin effective self efficacy against entrepreneurship interest of 38.9%, meaning that there are still affecting l6,7% interest in entrepreneurship for example among others: fakfor environmental and social factors.